Mixing with native broadleaf trees modified soil microbial communities of Cunninghamia lanceolata monocultures in South China - Zheng, Fenglin; Gu, Jiawei; Lu, Dehao; Yang, Jiaman; Shuai, Xiaomai; Li, Cheng; Chen, Hongyue (Frontiers in Microbiology, 2024)
In South China, nutrient-poor soil has been a form of abiotic stress affecting forest ecosystems. Herein, we aimed to compare soil microbial diversity and community structure between the mixed Cunninghamia lanceolata-broadleaf forest and the pure C. lanceolata forest across different soil layers (0-20 cm and 20-40 cm) and to analyze the relationships between these characteristics and the chemical properties of soils. Using high-throughput sequencing technology, the microbial composition from each forest type was analyzed, and differentially abundant microbial markers were identified through Linear discriminant analysis effect size analysis. Network analysis was utilized to investigate symbiotic relationships among microorganisms, and network robustness was assessed by calculating network natural connectivity. Results demonstrated that the content of soil microbial biomass carbon and nitrogen, total phosphorus and pH in mixed forest stand were significantly higher than those in pure forest stand, except for available phosphorus in 0-20 cm layer.Simultaneously, the mixed C. lanceolata-broadleaf forest has a more homogeneous bacterial and fungal communities at different depth soil layer compared with the pure C. lanceolata forest, wherein the mixed forest recruited more diverse bacterial community at deep soil layer and reduced the diversity of fungal community at the shallow soil layer. Meanwhile, the mixed forest showed higher bacterial community stability while the pure forest showed higher fungal community stability. Moreover, bacterial communities showed significant correlations with various soil chemical indicators, whereas fungal communities exhibited correlations with only TP and pH. Therefore, the mixed C. lanceolata-broadleaf forest rely on their recruiting bacterial community to enhance and maintain the higher nutrient status of soil while the pure C. lanceolata forest rely on some specific fungi to satisfy their phosphorus requirement for survive strategy.